Endovascular intervention for deep venous thrombosis in patients with inferior vena cava filters. (October 2016) - Karageorgiou, John; Fowler, Kathryn; Vedantham, Suresh; Saad, Nael
Patients with inferior vena cava (IVC) filter-associated deep venous thrombosis (DVT) are a challenging subset of patients for endovascular intervention. Given the lack of available data pertaining to this clinical scenario, the purpose of this study was to evaluate the authors' experience with the use of endovascular treatment for DVT in patients with IVC filters. Primary aims included assessing the technical and clinical success, complications, and clinical patency in these patients. This was a retrospective single-center review of adult patients with IVC filters undergoing endovascular treatment of DVT between 1/2005 and 4/2014. Patient electronic medical records were reviewed for demographic data, anticoagulation status, symptoms, symptomatic extremities, extent of thrombosis, therapies received, technical and clinical success, and complications. Query yielded 82 patients (mean 53 years, range 18–96; 66% male), all of whom were included in our analysis. The majority of patients presented with lower extremity pain and swelling, with extensive clot burden despite the use of anticoagulant medication. Treatment elements utilized included pharmacologic lysis in 92%, mechanical thrombectomy in 77%, angioplasty in 63% and stent placement in 50% of patients. Interventions were technically successful in restoring flow in 87% of patients, and clinically successful in improving presenting symptoms in 79% of patients. By SIR criteria, 24% of patients experienced complications (categorized as 10% minor and 14% major). There were two deaths from intracranial hemorrhage. The probability of thrombosis-free survival at 1, 3, 6, 9 and 12 months was 0.85 (CI 0.74–0.93), 0.81 (CI 0.69–0.89), 0.74 (CI 0.62–0.83), 0.70 (CI 0.57–0.8) and 0.70 (CI 0.57–0.8), respectively. Endovascular interventions are usually effective in relieving symptoms in patients with DVT and pre-existing IVC filters. However, these outcomes are achieved with significant complication rates that may exceed those observed when endovascular therapy is provided for other DVT populations.